2008
DOI: 10.1158/0008-5472.can-08-0115
|View full text |Cite
|
Sign up to set email alerts
|

RhoA-Dependent Regulation of Cell Migration by the Tumor Suppressor hSNF5/INI1

Abstract: Malignant rhabdoid tumors (MRT) are extremely aggressive pediatric tumors caused by the inactivation of the hSNF5/INI1 tumor suppressor gene, which encodes a core member of the SWI/SNF chromatin remodeling complex. Roles for hSNF5/ INI1 in cell cycle and differentiation have been documented. Based on the observation that MRTs are highly invasive, we investigated a role for hSNF5/INI1 in cell migration. MRT cell lines exhibit high migration properties that are dramatically reduced upon hSNF5/INI1 expression. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 46 publications
(63 reference statements)
4
25
0
Order By: Relevance
“…10 Rho GTPases have been implicated in many basic cellular processes that influence cell proliferation, motility, chemotaxis, and adhesion. 11 RhoA activates ROCK1 and LIMK to regulate actin cytoskeleton in the formation of stress fibers 12,13 and also induces adhesion 14 and migration 15 of cancer cells. Rac1 exerts its activity through phosphorylation and activation of PAK 16 and has been implicated in a wide range of biologic activities, including the control of cell growth, cytoskeletal reorganization, cell migration, and also in adhesion of endothelial cells 17 and neurons 18 and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…10 Rho GTPases have been implicated in many basic cellular processes that influence cell proliferation, motility, chemotaxis, and adhesion. 11 RhoA activates ROCK1 and LIMK to regulate actin cytoskeleton in the formation of stress fibers 12,13 and also induces adhesion 14 and migration 15 of cancer cells. Rac1 exerts its activity through phosphorylation and activation of PAK 16 and has been implicated in a wide range of biologic activities, including the control of cell growth, cytoskeletal reorganization, cell migration, and also in adhesion of endothelial cells 17 and neurons 18 and neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, deregulation of expression of known SNF5 targets, such as CCND1, GLI1, RHOA, AURKA and c-MYC, without evidence of genetic amplification suggests that epigenetically based alteration of gene expression is a key mechanism of SNF5-mediated tumor suppression. 22,[24][25][26][27]43,44 SWI/SNF complexes are specifically enriched at promoters, where they contribute to chromatin remodeling that facilitates epigenetic control of gene expression. 45 Thus, defective remodeling, perhaps akin to "epigenetic instability," caused by SNF5 loss could conceivably deregulate many target genes and activate pathways that cooperatively drive cancer growth, thus amplifying the effects of inactivation of a single gene and providing an explanation for the rapid tumorigenesis caused by SNF5 loss.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, BIN1 has been shown to genetically interact with Rho GTPases and could conceivably contribute to the increased Rho activity observed in RT cells. 44,52,53 Finally, while the cellular function of BIN1 is not completely understood, its ability to interact with many binding partners through its SH3 domain and its ability to translocate to the nucleus suggests that BIN1 may be an example of a bridge between epigenetic gene regulation and transduction of multiple types of extracellular signals. 30,54,55 Disruption of such coordinated signaling activity following SNF5 loss would be analogous to our finding that upstream control of Hedgehog signaling becomes uncoupled from Hedgehog target gene transcription in the absence of SNF5, using comparative marker selection (two-sided t-test with 1,000 permutations).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the role of SWI/ SNF in melanoma cell migration and invasion is not clear. One study showed that overexpression of SNF5 reduces cell migration properties in a RhoA-dependent manner in malignant rhabdoid tumor cells (25), whereas Sun et al (32) showed that overexpression of BRG1 and BRM enhances prostate cancer cell invasion. Therefore, more studies are required on the role of SNF5 in melanoma cell invasion, for instance, whether SNF5 regulates the expression and activity of matrix metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that SNF5 is able to regulate the balance between cell proliferation and differentiation (24). Finally, the invasive property of malignant rhabdoid tumor is dramatically reduced upon SNF5 expression in a RhoA-dependent manner (25). In contrast, inactivation of SNF5 caused murine embryonic fibroblasts and HeLa cells to undergo G 1 cell cycle arrest, followed by a p53-dependent apoptotic response (26,27).…”
mentioning
confidence: 99%